Numerical Simulation on Shoreline Change in Western Region of Badung Regency, Bali, Indonesia - Triwahyuni, Andhita; Asai, Koji (Journal of Environment; Vol 1 No 1, 2014)
Shoreline change is considered the most dynamic processes in coastal region. Coastal erosion is a global problem where 70% beaches around the world are recessional. Almost all coastal area in Bali is potential to suffer from erosion. Badung Regency in Bali has many beaches that famous as tourism area where from about 64 km shoreline length, 11,5 km were recorded suffered by erosion in 1985 and 12,1 km erosion in 2007. This study aims to determine the value of shoreline changes that occur in western of Badung Regency from 2001 to 2010 based on the predicted wave data using monthly wind data from Ngurah Rai, Tuban, Badung, Bali meteorological station. Shoreline change simulation measured the forward (accretion) or backward (erosion) distance of the shoreline on the East-West direction. Bali has wind patterns that influenced by the Northwest monsoon from November-April and Southeast monsoon from May-October. In 2001-2010, dominant wind in this region was coming from east, southeast, and west. Geographically western coast of Badung influenced by incoming winds from the west, southwest, and south. Wind blow towards the coast in 2001-2010 are dominantly come from the west with wind speed range was about 1,7-4,7 m/s. Simulation indicated that generally shoreline tends to experience accretion in the north and erosion in the south. From 16000 m of study shoreline, along 7100 m of shoreline tend to suffer by erosion. Oppositely, along 8900 m of shoreline tend to have accretion.
Keywords: wind distribution pattern; shoreline change; accretion; erosion